A review on nanofluid: preparation, stability, thermophysical properties, heat transfer characteristics and application - Ali, Abu Raihan Ibna; Salam, Bodius (SN applied sciences, 2020)
Nanofluid is a suspension of nanoparticles which is promising heat transfer fluid in the heat transfer enhancement having a plethora of applications because of its superior thermal conductivity and rheological properties. This paper points out the previous studies and recent progress in the improvement of heat transfer using nanofluid. The recent progresses on preparation and enhancement of stability were reviewed. Thermophysical, heat transfer characteristics of nanofluid and different factors such as particle size, shape, surfactant, temperature, etc. on thermal conductivity were presented. The present study reveals potential applications by utilizing nanofluid such as heat exchanger, transportation cooling, refrigeration, electronic equipment cooling, transformer oil, industrial cooling, nuclear system, machining operation, solar energy and desalination, defense, etc. Few barriers and challenges were also addressed. Finally, the challenges and further research opportunities were presented.